Analysis of KRAS, NRAS, BRAF, PIK3CA and TP53 mutations in a large prospective series of locally advanced rectal cancer patients. Issue 1 (5th July 2019) - Sclafani, Francesco; Wilson, Sanna Hulkki; Cunningham, David; Gonzalez De Castro, David; Kalaitzaki, Eleftheria; Begum, Ruwaida; Wotherspoon, Andrew; Capdevila, Jaume; Glimelius, Bengt; Roselló, Susana; Thomas, Janet; Tait, Daina; et al.
Abstract : Little information is available on the clinical significance of cancer‐related genes such as KRAS, NRAS, BRAF, PIK3CA and TP53 in nonmetastatic rectal cancer. We investigated mutations of these genes in a large prospective series of locally advanced rectal cancer (LARC) patients who were recruited into two phase II trials. Mutational analyses were performed with diagnostically validated methods including polymerase chain reaction, capillary electrophoresis single‐strand conformational analysis, Sanger sequencing and next‐generation sequencing. Associations between single or multiple gene mutations and clinicopathological characteristics and treatment outcomes were explored. Of these 269, 210 (78%) patients were assessable. Mutations of KRAS, NRAS, BRAF, PIK3CA and TP53 occurred in 43, 9, 4, 9 and 60% of patients, respectively. Concordance between paired biopsy and resection specimens was 82% for KRAS, 95% for NRAS, 99% for BRAF, 96% for PIK3CA and 63% for TP53. TP53 mutations were associated with extramural venous invasion on baseline MRI (78% vs . 65%, p = 0.04), poor pathological tumour regression (23% vs . 36%, p = 0.05) and a trend toward a worse 5‐year progression‐free survival (PFS; 60% vs . 74%, HR 1.59, p = 0.06). Patients with tumours harbouring mutation of TP53 and either KRAS or NRAS (32%) had a worse 5‐year PFS than those with TP53/KRAS / NRAS wild‐type tumours (54% vs . 72%, HR 1.75, p = 0.02). In univariate analysis, BRAF mutation predicted poor 5‐year overall survival only among patients treated without cetuximab (20% vs . 73%, HR 3.29, p = 0.03). This is one of the largest biomarker studies in a prospective, largely homogeneous, LARC population. Our findings are hypothesis generating and require validation in independent series. Abstract : What's new? Mutational analysis of cancer‐related genes can yield critical insight into therapeutic response and disease prognosis in patients with advanced metastatic colorectal cancer (CRC). The ability of mutational analysis to predict disease progression in nonmetastatic rectal cancer however, remains uncertain. Here, investigation of the significance of mutations in cancer‐related genes in nonmetastatic rectal cancer patients reveals an association specifically between TP53 mutation and poor tumour regression following neoadjuvant treatment. Survival was especially poor in patients with concomitant mutations in TP53 and RAS . The findings are relevant to the future generation of risk‐stratified investigational treatment approaches for nonmetastatic rectal cancer.